Superoperator Approach to the Lindbladian Dynamics of a Mirror-Field System - Marco A. García-Márquez; Héctor M. Moya-Cessa (Quantum Reports, 2025)
We use superoperator techniques to solve the master equation for the interaction between a single-mode quantized field and a single mechanical mode of a moving mirror, which is coupled to a zero-temperature reservoir that damps its amplitude. The solution we provide allows for its application in any initial state of the combined system. Furthermore, we obtain solutions to the stationary master equation for an initial number state for the field that is consistent with the result obtained for the average number of phonons.